Oral Tolerance Induced by Heat Shock Protein 65-Producing Lactococcus lactis Mitigates Inflammation in Leishmania braziliensis Infection - Guerra, Priscila Valera (2021)
CNPq grants numbers 428371/ 2018-3 and 304876/2019-4. PVG received a pos-doc fellowship from Funda̧cão Oswaldo Cruz, Programa Inova. VAA, TUM, AMCF, and CIB are senior investigators of CNPq. This study is financed in part by the Coordena̧cão de Aperfei̧coamento de Pessoal de Nıveĺ SUperior (CAPES)-Brazil, Finance Code 001.